Pengaruh Kemampuan Akademik Micro Teaching Terhadap Kemampuan Real Teaching Mahasiswa Program Studi Pendidikan Ekonomi Angkatan 2014 - Fransiskus Korosando; Maria Anita Bada (Ekspektasi: Jurnal Pendidikan Ekonomi, 2019)
Micro learning activities (micro teaching) in the Economic Education Study Program is a process of transforming science to shape the character of prospective teacher students who have specific teaching skills before implementing a real teaching program. Pragmatically, mastery of the material is less comprehensive, mastery of classes is less than optimal, awkwardness and awkwardness become modes of learning in micro teaching. It is also influenced by the limitation of the frequency of teaching micro. The acquisition of good / excellent grades in micro teaching activities cannot be used as a contribution to say that a 2014 Class of Economics Education Study Program student will be able to carry out real teaching programs well.